2007
DOI: 10.1007/s10961-006-9014-y
|View full text |Cite
|
Sign up to set email alerts
|

Faculty Entrepreneurs and Research Productivity

Abstract: In this paper, we analyze the research productivity of faculty entrepreneurs at 15 research institutes using a novel database combining faculty characteristics, licensing information, and journal publication records. We address two related research questions. First, are faculty entrepreneurs more productive researchers (“star scientists”) compared to their colleagues? Second, does the productivity of faculty entrepreneurs change after they found a firm? We find that faculty entrepreneurs in general are more pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
1
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(64 citation statements)
references
References 24 publications
3
57
1
3
Order By: Relevance
“…Lower supportiveness of the middle levels could perhaps be viewed as a manifestation of the tension caused by the perceived infringement of commercialisation on academic goals such as publication rate and completion of PhD projects. However, it is important to note that previous studies have shown a positive relation between commercialisation activities and both publishing rate and quality, in Europe as well as in US (Czarnitzki et al 2007;Lowe and Gonzalez-Brambila 2007 (Siegel et al 2003). The overwhelming majority of PhD students are not mobile during their doctoral education.…”
Section: Concluding Discussion and Implicationsmentioning
confidence: 95%
“…Lower supportiveness of the middle levels could perhaps be viewed as a manifestation of the tension caused by the perceived infringement of commercialisation on academic goals such as publication rate and completion of PhD projects. However, it is important to note that previous studies have shown a positive relation between commercialisation activities and both publishing rate and quality, in Europe as well as in US (Czarnitzki et al 2007;Lowe and Gonzalez-Brambila 2007 (Siegel et al 2003). The overwhelming majority of PhD students are not mobile during their doctoral education.…”
Section: Concluding Discussion and Implicationsmentioning
confidence: 95%
“…Previous research highlights that 'star scientists' (i.e. academics who publish more and/or publish papers with greater impact) are more likely to show successful commercialization of research results (Lowe and Gonzalez-Brambila, 2007;Zucker and Darby, 1996), which indicates a positive relationship between scholarly and commercial success. Having a star scientist leading the group may attract the attention of non-academic agents more interested in collaborating with scientists with good academic reputation or high research impact.…”
Section: Star Scientistsmentioning
confidence: 99%
“…Schartinger et al (2001Schartinger et al ( , 2002 measure department research quality using number of publications in foreign scholarly journals per researcher; they find that international publications are positively related to higher departmental engagement in joint research activities, but not to contract research or personnel mobility. Lowe and Gonzalez-Brambila (2007) conduct an individual-level study measuring researchers' productivity as number of journal articles published per year, and conclude that entrepreneurial faculty are more productive than their peers. Finally, Landry et al (2010) analyse possible complementarities among different activities and show that academic publication and consulting are positively related.…”
Section: Star Scientistsmentioning
confidence: 99%
“…They also found that professors who started companies were more than 10 times more likely to be "superstars" (as measured by citations to their papers) than their peers who had not started companies (7). " " ented a lot did so because they wanted to change society (8).…”
Section: New Products Presentmentioning
confidence: 99%